The effect of tightness on wages at the regional level in three Central European countries - Lajos Tamás Szabó (Magyar Nemzeti Bank, 2019)
In this paper, I examine the effect of tightness on wages in three Central European countries. The estimation is relevant for at least three reasons. Firstly, it is a novel exercise to check the implication of the Mortansen-Pissarides model on Central European data. Secondly, from the central bank's perspective it is important to know the effect of tightness on wages, since these are the major determinants of cost-push inflation. Thirdly, the magnitude of the spillover effect from tightness to wages can help determine the efficiency of a targeted development policy. My contribution is directly identifying the effect of tightness on wages from regional heterogeneity. I examine the effect of tightness on wages in Hungary, Slovakia and Poland using panel IV method on district level data. The direct effects are similar in the three countries, i.e. there is a positive link between tightness and wages. The magnitudes are somewhat different in Poland then in Hungary and Slovakia. There is spatial spillover effect in Hungary but this indirect effect is missing in Poland and Slovakia.
Keywords: J31; J61; J63; J64; 330; local labour markets; labour market tightness; wage equation